2008
DOI: 10.1177/147323000803600605
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Stimulation in Obese and Non-Obese Polycystic Ovary Syndrome Using a Low-Dose Step-Up Regimen with Two Different Starting Doses of Recombinant Follicle-Stimulating Hormone

Abstract: Sixty-seven infertile women with polycystic ovary syndrome (PCOS) were divided into two groups, obese and nonobese, according to their body mass index. Waist-to-hip ratio, insulin resistance, total testosterone and dehydroepiandrosterone sulphate levels were significantly elevated in obese, compared with non-obese, patients. Both groups were treated with a low-dose step-up protocol of recombinant follicle-stimulating hormone (rFSH) with a starting dose of 50 IU/day and, every third day, a 25-IU increase in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Adiponectin has many functions (174), including its ability to promote oocyte maturation and blastocyst formation (175), and is reduced in the circulation of women with PCOS (176), together with tumor necrosis factor-α-induced dysregulation of adiponectin secretion by PCOS adipocytes in vitro (177). In addition, leptin impairs FSH-stimulated steroidogenesis in human granulosa cells, thereby reducing ovarian responsiveness to FSH (178181). Obesity also lowers LH pulse amplitude and alters LH pharmacokinetic structure (182, 183), contributing to reduced serum LH levels in obese women with PCOS (184, 185), who may be more susceptible to the modulatory effects of insulin excess than LH.…”
Section: Antral Follicle Developmentmentioning
confidence: 99%
“…Adiponectin has many functions (174), including its ability to promote oocyte maturation and blastocyst formation (175), and is reduced in the circulation of women with PCOS (176), together with tumor necrosis factor-α-induced dysregulation of adiponectin secretion by PCOS adipocytes in vitro (177). In addition, leptin impairs FSH-stimulated steroidogenesis in human granulosa cells, thereby reducing ovarian responsiveness to FSH (178181). Obesity also lowers LH pulse amplitude and alters LH pharmacokinetic structure (182, 183), contributing to reduced serum LH levels in obese women with PCOS (184, 185), who may be more susceptible to the modulatory effects of insulin excess than LH.…”
Section: Antral Follicle Developmentmentioning
confidence: 99%
“…A low-dose Gn stimulation strategy for PCOS patients was recommended (16). As previously reported, it was suggested that a low starting Gn dose of < 150 IU/day and 25-IU incremental doses every third day should be considered in a COS protocol for PCOS patients with a high HOMA-IR score (42). It is necessary to decide on both the initial Gn dose and the incremental dose when a low-dose step-up regimen is used.…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative pregnancy rate after six treatment cycles was 53.1%, and 6.0% of the 136 clinical pregnancies were twins (Calaf Alsina et al, 2003). Another cohort study with a focus on BMI included 67 patients with PCOS in a low-dose step-up protocol with a starting dose of 50 IU recombinant FSH/day (Yildizhan et al, 2008). The median threshold recombinant FSH dose was 50 IU/day in non-obese (BMI <25 kg/m 2 ) patients compared with 75 IU/day in obese (BMI ≥25 kg/m 2 ) patients (P < 0.01).…”
Section: Gonadotrophinsmentioning
confidence: 99%